2021
DOI: 10.3390/v13122387
|View full text |Cite
|
Sign up to set email alerts
|

Drugs of Abuse and Their Impact on Viral Pathogenesis

Abstract: Commonly misused substances such as alcohol, cocaine, heroin, methamphetamine, and opioids suppress immune responses and may impact viral pathogenesis. In recent years, illicit use of opioids has fueled outbreaks of several viral pathogens, including the human immunodeficiency virus (HIV), hepatitis B virus (HBV), and hepatitis C virus (HCV). This review focuses on the myriad of mechanisms by which drugs of abuse impact viral replication and disease progression. Virus–drug interactions can accelerate viral dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 209 publications
(218 reference statements)
0
3
0
Order By: Relevance
“…There is growing evidence that drugs such as methamphetamine, cocaine, opioids, and marijuana increase HIV, HBV, and HCV replication both in vitro and in animal models [ 87 , 88 , 89 ]. Several mechanisms contribute to the decreased ability to control pathogens and limit their subsequent clearance, including the impaired function of natural killer cells, T-cells, B-cells, neutrophils, dendritic cells, macrophages, the altered expression of cytokines and chemokines, as well as weak intestinal barrier integrity [ 86 , 90 ]. Drugs of abuse can impair immune system functions, affecting both innate and adaptive immunity.…”
Section: Drugs Of Abuse and The Immune Systemmentioning
confidence: 99%
“…There is growing evidence that drugs such as methamphetamine, cocaine, opioids, and marijuana increase HIV, HBV, and HCV replication both in vitro and in animal models [ 87 , 88 , 89 ]. Several mechanisms contribute to the decreased ability to control pathogens and limit their subsequent clearance, including the impaired function of natural killer cells, T-cells, B-cells, neutrophils, dendritic cells, macrophages, the altered expression of cytokines and chemokines, as well as weak intestinal barrier integrity [ 86 , 90 ]. Drugs of abuse can impair immune system functions, affecting both innate and adaptive immunity.…”
Section: Drugs Of Abuse and The Immune Systemmentioning
confidence: 99%
“…Furthermore, illicit opioid use has fueled outbreaks of several viruses, particularly HIV, HBV, and HCV. Previous studies have demonstrated that virus-drug interactions can accelerate viral pathogenesis, not only increasing transmission but also suppressing immune responses [20]. In longitudinal studies of people living with HIV, dangerous drug abuse was correlated with failure to maintain the viral load [21].…”
Section: Drugs Of Abuse and Opioidsmentioning
confidence: 99%
“…At present, it is clear that although viruses are not the only cause of tumors, they play a large role in the occurrence of malignant neoplasms (for instance, the presence of hepatitis B virus increases the risk of developing hepatocellular carcinoma) in both humans and animals. A characteristic feature of tumor diseases associated with viruses is a long latent period, years and even decades can pass from the moment of infection to the manifestation of the disease ( Mui et al, 2019 ; Blackard and Sherman, 2021 ).…”
Section: Polyphenols and Virusesmentioning
confidence: 99%